2017
DOI: 10.1097/bot.0000000000000701
|View full text |Cite
|
Sign up to set email alerts
|

Higher Charlson Comorbidity Index Scores Are Associated With Increased Hospital Length of Stay After Lower Extremity Orthopaedic Trauma

Abstract: Prognostic Level III. See Instructions for Authors for a complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Thus, our finding of increased comorbidity burden and lower pain levels should be interpreted cautiously. With respect to rehabilitation LOS, however, our findings are consistent with prior studies that have shown that the CCI can be used as a predictive tool . As the medical complexity of a patient increases, the possibility that a comorbid condition is exacerbated or contributory to decreased physical tolerance increases.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, our finding of increased comorbidity burden and lower pain levels should be interpreted cautiously. With respect to rehabilitation LOS, however, our findings are consistent with prior studies that have shown that the CCI can be used as a predictive tool . As the medical complexity of a patient increases, the possibility that a comorbid condition is exacerbated or contributory to decreased physical tolerance increases.…”
Section: Discussionsupporting
confidence: 89%
“…Our results also indicate that CCI is associated with longer LOS and higher hospitalisation costs in Australia. CCI has previously been found to predict LOS in stroke patients [ 39 ], as well as in patients with cancer [ 38 ], sepsis, or those undergoing surgical procedures [ 40 ]. Among patients hospitalised for hip fracture in the USA, Johnson and colleagues [ 41 ], observed that patients with a CCI score of 2, on average, stayed 1.92 extra days in the hospital and incurred USD$8698 extra costs compared to those with a CCI score of 0.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative steroid use may be related to the relatively more preoperative comorbidities found in the patients. Studies on lower extremity fracture surgeries revealed that the CCI was positively correlated with the number of days that patients were hospitalized, [35,36] and that on average, patients with a CCI of 2 spent 1.92 more days in hospitals than those with a CCI of 0. [35] For type of anesthesia received, the effects of general and regional anesthesia on overall postoperative complications and the length of stay were inconclusive.…”
Section: Discussionmentioning
confidence: 99%